Role of Prehabilitation in Patients Undergoing Cancer Surgeries - Deepti Ahuja; Rakesh Garg (Research and Practice in Anesthesiology, 2017)
Cancer is the second leading cause of death worldwide and nearly 1 in 6 deaths is due to cancer. It accounts for 8.8 million deaths in 2015. The occurrence of cancer is increasing and new cases are expected to rise by about 70% over the next 2 decades.1 With the advances in diagnostic and therapeutic procedures, more number of cancer patients will undergo curative surgical procedures. However, the mortality and morbidity rates after major oncological surgical resection are still high and range between 4%-10% and 20%-60%, respectively